2006
DOI: 10.1007/s00418-006-0155-8
|View full text |Cite
|
Sign up to set email alerts
|

The expression of neurotrophins and their receptors in the prenatal and adult human testis: evidence for functions in Leydig cells

Abstract: Previous studies have demonstrated local functions for neurotrophins in the developing and mature testis of rodents. To examine whether these signaling molecules are present and also potentially active in the human testis, we characterized immunohistochemically the expression and cellular localization of the known neurotrophins and their receptors during prenatal testicular development as well as in the adult human testis. Results obtained revealed the presence of nerve growth factor (NGF), brain-derived neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 54 publications
5
36
0
Order By: Relevance
“…Immunohistochemical analysis revealed the presence of TRKA in the membranes of Leydig cells (Djakiew et al 1994), a result that was supported by the subsequent finding that TrkA transcripts were present in Leydig cells but not in the germ cells in mouse testes (Seidl et al 1996). It has also been demonstrated that the Leydig cells are the primary sites of NGF/TRKA expression in both fetal and adult human testes (Müller et al 2006), although the Sertoli cells and some cellular elements of the germinative epithelium were also TRKA positive (Koeva et al 1999). These findings suggest that NGF may regulate testicular development and spermatogenesis via both autocrine and paracrine pathways.…”
Section: The Roles Of Neurotrophins In Testicular Developmentsupporting
confidence: 56%
“…Immunohistochemical analysis revealed the presence of TRKA in the membranes of Leydig cells (Djakiew et al 1994), a result that was supported by the subsequent finding that TrkA transcripts were present in Leydig cells but not in the germ cells in mouse testes (Seidl et al 1996). It has also been demonstrated that the Leydig cells are the primary sites of NGF/TRKA expression in both fetal and adult human testes (Müller et al 2006), although the Sertoli cells and some cellular elements of the germinative epithelium were also TRKA positive (Koeva et al 1999). These findings suggest that NGF may regulate testicular development and spermatogenesis via both autocrine and paracrine pathways.…”
Section: The Roles Of Neurotrophins In Testicular Developmentsupporting
confidence: 56%
“…Neurotrophins are mainly studied on nervous cells; however, as multifunctional growth factors, they can exert various effects through their receptors on non-neuronal cells such as kidney (Caroleo et al 2015), testis (Müller et al 2006), thymus (Maroder et al 2000), lymph node (García-Suárez et al 1997), skin (Di Marco et al 1993), spleen (Pérez-Pérez et al 2004), ovary (Seifer et al 2006), salivary glands and mammary ducts (Shibayama and Koizumi 1996;Sariola 2001).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, p75NTR transmits both positive and negative signals (Reichardt, 2006). To date, neurotrophins have been mainly studied in nervous cells, but, as multifunctional growth factors, they can exert various effects through their receptors on non-neuronal cells such as testis (Müller et al, 2006), thymus (Maroder et al, 2000), skin (Di Marco et al, 1993), salivary glands and mammary ducts (Shibayama and Koizumi, 1996;Sariola, 2001) and ovine mammary glands (Colitti, 2015). It is noteworthy that, because NGF and BDNF are secreted by WAT and BAT (Sornelli et al, 2009) and their levels in the circulation and tissue are altered in cardiometabolic diseases , neurotrophins are considered as metabotrophic factors, implicating in metabolic diseases (Chaldakov et al, 2010).…”
mentioning
confidence: 99%